HUBUNGAN MEKANISME KOPING DENGAN STRES KERJA PERAWAT IGD DAN ICU DI RSUD ULIN BANJARMASIN - Yeni Mulyani; Evi Risa M; Littia Ulfah (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2017)
The emergency department and intensive care unit is one of central service in hospital and also the part of hospitals that requires skill and educated nurses in providing health services to patients. The demands that must be fulfilled by nurses, both critical care nurses and emergency nurses can cause distress and can become the source of stressor for nurses. If the nurses have no effective coping it will cause working stress. This study aimed to determine the the relationship between coping mechanism with working stress among emergency and critical care nurses in Ulin Banjarmasin Hospital.This is a quantitative research, with correlative study design. The population of this study were emergency and critical nurses as many as 67 respondents using the total sampling technique obtained 62 respondents who are willing to be respondents. The results were analyzed by Chi-Square test.The results showed that most nurses had minor working stress with adaptive coping mechanism as many as 43 respondents (72,9%). The Chi-Square test results show probability value of 0.026 is smaller than the significance level used 5% (0.026 <0.05), so it can be concluded that there is a relationship between coping mechanism with working stress of emergency and critical nurses in Ulin Banjarmasin Hospital. It is known that most respondents who have maladaptive coping will tend to experience more severe stress.Therefore, researchers suggest the nurses to perform a reducing stresss activity either relaxation techniques, recreation, or exercise. Increase the knowledge either through education or skills upgrading through specialized training. Suggestion for hospital organization to do assessment on work load and arrangement of nurse amount with nurse competence in emergency and ICU so that it can decrease excessive work load and decrease nurse work stress level and hold special education and training program as needed and demand of work in the ward periodically. Keywords : Nurse, Coping Mechanism, Working Stress